1998
DOI: 10.1128/mcb.18.8.4752
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Role for U2AF-SAP 155 Interactions in Recruiting U2 snRNP to the Branch Site

Abstract: Base pairing between U2 snRNA and the branchpoint sequence (BPS) is essential for pre-mRNA splicing. Because the metazoan BPS is short and highly degenerate, this interaction alone is insufficient for specific binding of U2 snRNP. The splicing factor U2AF binds to the pyrimidine tract at the 3 splice site in the earliest spliceosomal complex, E, and is essential for U2 snRNP binding in the spliceosomal complex A. We show that the U2 snRNP protein SAP 155 UV cross-links to pre-mRNA on both sides of the BPS in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
290
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 274 publications
(312 citation statements)
references
References 39 publications
(70 reference statements)
21
290
0
1
Order By: Relevance
“…It is likely that stronger BP 0 (in terms of U2 snRNA complementarity) can compensate for lower AG affinity to U2AF, leading to the recognition of BP 0 in a U2AF-independent manner (or less dependent than in the case of canonical BP). This model is supported by our U2AF depletion experiments and is consistent with previous findings that BP recognition may depend or not on AG binding to U2AF35, according to BP and 3 0 ss sequence and organization 11,[16][17][18] . In contrast, SF3B1 WT may allow a more promiscuous binding of U2 snRNA to both canonical and alternative BPs, and in this case, the final choice of BP may be determined by context, especially 3 0 ss affinity for U2AF.…”
Section: Discussionsupporting
confidence: 80%
“…It is likely that stronger BP 0 (in terms of U2 snRNA complementarity) can compensate for lower AG affinity to U2AF, leading to the recognition of BP 0 in a U2AF-independent manner (or less dependent than in the case of canonical BP). This model is supported by our U2AF depletion experiments and is consistent with previous findings that BP recognition may depend or not on AG binding to U2AF35, according to BP and 3 0 ss sequence and organization 11,[16][17][18] . In contrast, SF3B1 WT may allow a more promiscuous binding of U2 snRNA to both canonical and alternative BPs, and in this case, the final choice of BP may be determined by context, especially 3 0 ss affinity for U2AF.…”
Section: Discussionsupporting
confidence: 80%
“…2A). SF3B1, which was previously shown to directly bind substrate mRNAs and affect Bcl-x AS (Gozani et al 1998;Massiello et al 2006) and was herein identified in PQBP1 affinity purifications (Supplemental Table S1), constituted a prime candidate to work together with PQBP1. Consistent with this hypothesis, depletion of PQBP1 decreased SF3B1's association with Bcl-x mRNA (Fig.…”
Section: Pqbp1 Affects U2 Snrnp Component Sf3b1 Functionmentioning
confidence: 99%
“…Previous studies in human and yeast extracts using hydroxy radical cleavage or protein-RNA crosslinking led to the hypothesis that the 5′SS and BS regions are closely positioned in early complexes containing only U1 and/or U2 (6)(7)(8)(9)(10)(11)(12). However, as both of these irreversible trapping methods can capture transient excursions that are not necessarily on the pathway for splicing, when during spliceosome assembly and activation the 5′SS and BS are stably juxtaposed has remained unclear.…”
mentioning
confidence: 99%